Analysis of comorbid characteristics, molecular mechanisms between mild cognitive impairment and Alzheimer’s disease with interventions in a community-based population in Shanghai - Sun, Yiying; Liu, Bin; Tong, Jie; Shi, Dianhong; Zhu, Xiaochun; Jiang, Tingting; Yang, Yi; Sun, Xirong (Frontiers in Neurology, 2026)
BackgroundMild cognitive impairment (MCI) is a critical early stage of Alzheimer’s disease (AD). Elucidating the comorbidity characteristics, influencing factors, and molecular mechanisms between MCI and AD in community-based populations is crucial for early intervention in cognitive impairment.Methods2,234 elderly individuals aged 50 years or older from 14 communities in Pudong New District, Shanghai, were enrolled in this study. The Montreal Cognitive Assessment (MoCA), Mini-Mental State Examination (MMSE), and Clinical Dementia Rating (CDR) were used to divide individuals into a control group (n = 1,160) and an MCI group (n = 1,074). The associations of demographic characteristics, lifestyle, and psychological status with MCI were analyzed. Transcriptome data from GSE140829 (training set) and GSE63060 (validation set) were obtained from the GEO database. Weighted gene co-expression network analysis (WGCNA) was used to identify MCI signature genes. KEGG pathway analysis was combined with the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway to elucidate mechanisms of comorbidity. Targeted intervention agents were screened based on the DSigDB database. Molecular docking (MD) was used to evaluate the binding ability between small molecules and target proteins.ResultsThe prevalence of AD in the MCI group (30.17%) was significantly higher than that in the control group (p < 0.001), and MCI and AD were significantly positively correlated. Age, gender, smoking, living arrangements, mobile phone use, pet ownership, stress, anxiety, and depression were key influencing factors for MCI (p < 0.05). The proportion of individuals living with children and grandchildren (57.45%) in the MCI group was significantly higher than that in the control group (16.29%) (p < 0.001). WGCNA identified 273 MCI signature genes. KEGG pathway analysis showed that these genes were significantly enriched in neurodegenerative disease pathways, including AD pathways (with the AD pathway ranking first in the “Human Diseases” category). Targeted intervention screening identified the natural compounds boldine (comprehensive score 961.58) and piceatannol (comprehensive score 358.46) as potential drug candidates (p < 0.05), both of which have strong binding ability to target proteins.ConclusionMCI patients in the community are at high risk of AD, and their comorbidity characteristics are affected by multidimensional lifestyle and psychological factors. Boldine and piceatannol may be potential natural compounds for the intervention of cognitive impairment. The results of this study can provide a theoretical basis for the early prevention and precise intervention of cognitive impairment in the community.